2021
DOI: 10.3390/ijerph182211801
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequities in LGBT People and Nursing Interventions to Reduce Them: A Systematic Review

Abstract: Background: Lesbian, gay, bisexual, and transgender (LGBT) people present poorer mental and physical health results compared to the heterosexual and cisgender population. There are barriers in the healthcare system that increase these health inequities. Objective: To synthesise the available evidence on how nurses can intervene in reducing health inequities in LGBT people, identifying their specific health needs and describing their experiences and perceptions of the barriers they face in the healthcare system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 31 publications
0
45
0
10
Order By: Relevance
“…This is especially significant considering people from traditionally marginalized groups are not as likely to enroll in hospice care and if they do, they tend to receive a lower quality of care. Medina-Martínez et al (2021) noted health disparities occurring among the LGBTQIA population resulting from a lack of cultural competence. The authors identified interventions that could be applied in nursing curricula such as inclusive sex education, defining sexual and gender diverse populations, and prevention of suicide and bullying.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially significant considering people from traditionally marginalized groups are not as likely to enroll in hospice care and if they do, they tend to receive a lower quality of care. Medina-Martínez et al (2021) noted health disparities occurring among the LGBTQIA population resulting from a lack of cultural competence. The authors identified interventions that could be applied in nursing curricula such as inclusive sex education, defining sexual and gender diverse populations, and prevention of suicide and bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are barriers in our healthcare systems that increase these health inequities. [3][4][5] Braybrook's paper 6 in this issue of BMJ Quality & Safety makes an important contribution to this work. It adds to a growing literature that addresses the experiences of LGBT+ people (and their significant others) at times of heightened need and vulnerability, facing serious illness and/or in need of palliative or end of life care (see, for example, references [7][8][9][10][11] ).…”
Section: Monitoring Patients' Sexual Orientation and Gender Identity:...mentioning
confidence: 99%
“…Suicide is a primary risk factor for mortality among men who have sex with men (MSM), and depression can increase a person’s suicidal thoughts ( Jadva et al, 2021 ). Research has reported considerable variation in the lifetime prevalence of suicidal thoughts among MSM, highlighting the critical need for a valid estimate of the pooled lifetime prevalence ( Goodyear et al, 2021 ; Medina-Martínez et al, 2021 ). Only two meta-analyses assessing the pooled lifetime prevalence of suicidal thoughts in MSM have been published, and none have been published since 2008 ( Patten et al, 2022 ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%